2018
DOI: 10.17557/tjfc.467468
|View full text |Cite
|
Sign up to set email alerts
|

EFFECT OF PHOSPHORUS FERTILIZER ON SOME YIELD COMPONENTS AND QUALITY OF DIFFERENT ANISE (Pimpinella anisum L.) POPULATIONS

Abstract: The objective of the study was to investigate the effect of phosphorus treatments on yield and quality traits of three anise populations with different origin under Bornova-Izmir conditions in 2016 and 2017. Phosphorus fertilizer was applied at the rate of 0, 30, 60 and 90 kg ha-1 to three different anise populations (Turkish, Spanish and Syrian). Field trials were arranged as split-plot in the Randomized Complete Block design with three replications. The plant characteristics such as plant height (cm), biomas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
2
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 6 publications
3
2
0
7
Order By: Relevance
“…High variability for important agronomic traits, i.e. days to silk, plant height, ear length, 1000-kernel weight and grain yield in our investigation was also supported by the results of previous studies (Sonmez, 2018 , 1999). Results for dry matter yield in this study do not resemble with the findings of Sabeena and Dar (2005), who reported the values ranged from 8150 to 12000 kg ha -1 for this trait.…”
Section: Discussionsupporting
confidence: 91%
“…High variability for important agronomic traits, i.e. days to silk, plant height, ear length, 1000-kernel weight and grain yield in our investigation was also supported by the results of previous studies (Sonmez, 2018 , 1999). Results for dry matter yield in this study do not resemble with the findings of Sabeena and Dar (2005), who reported the values ranged from 8150 to 12000 kg ha -1 for this trait.…”
Section: Discussionsupporting
confidence: 91%
“…(2015) kişnişte, Kumawat ve ark. (2015) rezenede, Sönmez (2018) ise anasonda yürüttükleri çalışmalarda belirli bir P düzeyinden sonra ana şemsiyedeki tohum sayısında önemli düşmelerin olduğu rapor edilmiştir. Artan P dozlarına bağlı olarak şemsiyede tohum sayısının arttığını bildiren çalışmalar da bulunmaktadır (Jan ve ark., 2011; Javiya ve ark., 2017; Pooja ve ark.,…”
Section: Araştırmamız Bulgularında Olduğu Gibi;unclassified
“…Fosforlu gübreleme ile ilgili olarak farklı bitkilerde yapılan benzer çalışmalar, araştırmamız bulgularını destekler niteliktedir. Örnek olarak; aspirde (Katar ve ark., 2011), pelemirde (Arslan ve ark., 2014), rezenede (Tunçtürk ve ark., 2011;Kumawat ve ark., 2015), anason bitkisinde (Sönmez, 2018) uygulanan P dozlarının tohum verimini kontrole göre arttırdığı rapor edilmiştir.…”
Section: Tohum Verimiunclassified
“…Yurdumuzda anason üretimi ve ekim alanları yıllara göre değişmekle birlikte genellikle Afyon, Antalya, Burdur, Denizli, Balıkesir, Bursa, Isparta, İzmir, Kütahya ve Muğla illerimiz sınırları içinde yetiştirilmekte olup anason ekiliş alanı, üretim miktarı ve verimi çok değişik faktörlerin etkisi ile stabil değildir (Bayram, 2019). Anason tarımının gelişmeyişi ve üretimin düşük olmasının nedenleri; anasonda üretimin popülasyon halinde olması, çiftçinin kalitesi yüksek ve verimli sertifikalı tohumluk bulamaması, üretimin genelde küçük aile işletmeciliği şeklinde yapılması, üretim tekniği, gübrelemesi ve zirai mücadelesi gibi konularda yeteri kadar bilgiye sahip olmaması, anason alım fiyatlarının düşük olması ve yıllara göre karlılığın değişmesi şeklinde sıralanabilir (Bayram, 1992 (Bayram, 1992;Boztaş;Sönmez, 2018) Araştırmada elde ettiğimiz bulgular; Bayram (1992), Boztaş (2018), Sönmez (2018)…”
Section: Introductionunclassified